Transfusions, major bleeding, and prevention of venous thromboembolism with enoxaparin or fondaparinux in thoracic surgery - Girard, Philippe; Demaria, Joelle; Lillo-Le Louët, Agnès; Caliandro, Raffaele; Guillou, Jean-Luc Le; Crespin, Malvina; Sanctis, Alice de; Stern, Jean-Baptiste (Thrombosis and Haemostasis, 2011)
Enoxaparin 40 mg/day (E) or fondaparinux 2.5 mg/day (F) are recommended to prevent venous thromboembolism (VTE) in medical and surgical patients at risk. Over the two years after switching from E to F in our 35-bed department of pulmonology and thoracic surgery, an increase in the number of transfusions was observed. A retrospective explanatory investigation was undertaken. Hospitalised patients in the two years before and after switching from E to F were compared. The files of all transfused patients were reviewed. A blinded independent committee adjudicated major bleeding events. In the investigated time period, the overall transfusion rate increased from 1.8% of 2,989 patients to 3.1% of 3,085 patients (p=0.002). Mean ages (58.4 vs. 59.1 years), proportions of surgical patients (63.6% vs. 58.4%), cancer patients (72.1% vs. 69.5%), and treated patients (≥1 dose of E or F: 51.8% vs. 52.5%) were similar. The number of medical patients transfused while receiving E or F did not increase significantly (0.9% vs. 1.3%, RR=1.45 [0.66–3.17], p=0.35). The number of surgical patients trans-fused postoperatively while receiving E or F increased significantly (0.7% vs. 1.9% of all surgical patients, relative risk [RR]=2.75 [1.45–5.23], p=0.001), including a significant increase in transfusions for major bleeding (0.2% vs. 0.9%, RR=5.97 [1.74–20.4], p<0.001). A multivariate analysis did not find confounding factors. The incidence of symptomatic postoperative pulmonary embolism remained very low (0.05% vs. 0.17%). In conclusion, in thoracic surgery patients, switch-ing from enoxaparin to fondaparinux to prevent VTE was associated with a significant increase in the risk of postoperative major bleeding. A causal relationship appears plausible.
Keywords: Venous thromboembolism; prevention; surgery; bleeding; enoxaparin; fondaparinux